2023
DOI: 10.3390/ijms241612838
|View full text |Cite
|
Sign up to set email alerts
|

Elexacaftor Mediates the Rescue of F508del CFTR Functional Expression Interacting with MSD2

Abstract: Cystic fibrosis (CF) is one of the most frequent lethal autosomal recessive diseases affecting the Caucasian population. It is caused by loss of function variants of the cystic fibrosis transmembrane conductance regulator (CFTR), a membrane protein located on the apical side of epithelial cells. The most prevalent CF-causing mutation, the deletion of phenylalanine at position 508 (F508del), is characterized by folding and trafficking defects, resulting in the decreased functional expression of the protein on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 50 publications
6
7
0
Order By: Relevance
“…MSD2 and NBD2 were detected as bands of ~47 and ~30 kDa, respectively. Controls in untransfected HEK-t cells showed that the primary As expected [38,[48][49][50][51], treatment with VX661 increased the expression of MSD1. Indeed, in HEK-t cells treated with VX661, the expression of this domain was 2.19 times higher than in control DMSO-treated cells.…”
Section: Assessing the Impact Of Correctors On Cftr Single Domain Exp...supporting
confidence: 64%
See 2 more Smart Citations
“…MSD2 and NBD2 were detected as bands of ~47 and ~30 kDa, respectively. Controls in untransfected HEK-t cells showed that the primary As expected [38,[48][49][50][51], treatment with VX661 increased the expression of MSD1. Indeed, in HEK-t cells treated with VX661, the expression of this domain was 2.19 times higher than in control DMSO-treated cells.…”
Section: Assessing the Impact Of Correctors On Cftr Single Domain Exp...supporting
confidence: 64%
“…Treatment with the corrector, VX661, or with 2a, 7m, and 7a did not change the expression of MSD2. On the contrary, as observed elsewhere [40,51], VX445 increased the expression of this domain to 2.51 times that observed in untreated control HEK-t cells (Figure 8E). Treatment with VX661 or VX445, or with each of the three hybrids, did not modify the expression level of NBD2 (Figure 8F).…”
Section: Assessing the Impact Of Correctors On Cftr Single Domain Exp...supporting
confidence: 59%
See 1 more Smart Citation
“…These findings suggested that elexacaftor most likely requires interaction with more than a single domain to exert its rescue effects, in an MoA probably affecting domain interfaces such as TMD1 and TMD2 assembly and their interface with NBD1 [ 125 ]. Bongiorno and co-authors [ 126 ] further explored the MoA of elexacaftor by assessing its effects on p.Phe508del-CFTR to identify the protein domains affected by this modulator. Using different biochemical approaches and plasmid constructs expressing the isolated domains, the authors suggested that different correctors can act on the expression and stability of distinct p.Phe508del-CFTR regions, identifying TMD2 as the primarily CFTR domain involved in p.Phe508del rescue by elexacaftor [ 126 ].…”
Section: Elexacaftor (Vx-445) and Triple Combination With Tezacaftor ...mentioning
confidence: 99%
“…Bongiorno and co-authors [ 126 ] further explored the MoA of elexacaftor by assessing its effects on p.Phe508del-CFTR to identify the protein domains affected by this modulator. Using different biochemical approaches and plasmid constructs expressing the isolated domains, the authors suggested that different correctors can act on the expression and stability of distinct p.Phe508del-CFTR regions, identifying TMD2 as the primarily CFTR domain involved in p.Phe508del rescue by elexacaftor [ 126 ].…”
Section: Elexacaftor (Vx-445) and Triple Combination With Tezacaftor ...mentioning
confidence: 99%